Medicare Reimbursement Changes for Ambulatory Surgery Centers and Remuneration to Urologic Physician-Owners - Strope, Seth A. (2008)
PURPOSE: In an effort to reduce the cost of surgical care, Medicare has introduced a new facility fee schedule for ambulatory surgical centers (ASCs). This prospective payment system increases reimbursement for many urologic procedures while decreasing reimbursement for others. All stakeholders: physicians, the Medicare program, and hospitals, will be affected by these changes. MATERIALS AND METHODS: Using the Agency for Healthcare Research and Quality’s State Ambulatory Surgery Databases, we identified Medicare patients in Florida undergoing urologic procedures in ASCs from 1998 to 2005. Three facility groupings were created: urology-dominant, multi-specialty, and other-specialty dominant. First, the impact of reimbursement changes at the procedure and facility levels was assessed using data from 2005. Projections of ASC utilization and reimbursement in 2008 were then generated using all available data. RESULTS: In 2008, we project total payments by Medicare to increase by $4,233,080 (26% Range 22% to 32%) under the new reimbursement system compared to the old system. At the facility level, reimbursement to multi-specialty facilities increases substantially (49% increase), while urology-specialty facilities receive less benefit (10% increase). Compared to multi-specialty facilities, urology-specialty facilities perform a higher proportion of cases where the reimbursement is set to decrease CONCLUSIONS: Under the new payment scheme for ASCs, winners and losers emerge. Facilities with diversified procedure mixes will find increased revenue, while those with less diversification will find slower growth to their revenue streams. Counter to the desire of the Medicare program to decrease surgical costs, the new program may increase the payments made for urologic surgery.